Menhaden fish oil encapsulation by spray drying process: influence of different biopolymer materials, inlet air temperature and emulsion ratios - Nurmaryam Aini, Hashim; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Siti Zubaidah, Sulaiman (Society of Chemical Industry, 2023)
BACKGROUND: Incorporating fish oils into commonly consumed foods is an emerging technique for increasing the daily intake of omega-3 fatty acid. However, the high vulnerability of fish oil towards oxidative deterioration reduces shelf life stability. Microencapsulation by spray drying with different combinations of biopolymers and other parameters may provide a solution by preventing further oxidation of fish oil and permitting its delivery to food items. This study emphasised the influence of developed biopolymer materials (maltodextrin, maltodextrin + gum arabic, maltodextrin + starch, maltodextrin + whey pro- tein isolates and maltodextrin + sodium caseinate) for emulsion formulation, inlet air temperature (160, 170, 180, 190 and 200 °C) and emulsion ratios (15, 20, 25, 30 and 35%) on the physicochemical properties of powdered menhaden fish oil by spray drying technique. RESULTS: Microencapsulated menhaden fish oil was evaluated for its moisture content, size distribution, microcapsule effi- ciency, peroxide value, free fatty acid, acid value and morphological structure. It was observed that the coating materials of maltodextrin + whey protein isolates gave the lowest moisture content and peroxide value of 4.410% and 4.031 mEq kg−1, respectively. The morphological images showed a smooth surface with no cracks and minimal shrinkage, indicating lower per- meability to gases and effectively protecting the oil against deterioration. CONCLUSION: The spray drying procedure using maltodextrin + whey protein isolates at an inlet air temperature 190 °C and emulsion ratio of 30% successfully produced fish oil microcapsules with improved properties.